Bioprospecting for the soil-derived actinobacteria and bioactive secondary metabolites on the Western Qinghai-Tibet Plateau - Liu, Lifang; Liu, Yuyu; Liu, Shaowei; Nikandrova, Arina A.; Imamutdinova, Arina N.; Lukianov, Dmitrii A.; Osterman, Ilya A.; Sergiev, Petr V.; Zhang, Benyin; Zhang, Dejun; Li, Feina; Sun, Chenghang (Frontiers in Microbiology, 2023)
The Western Qinghai-Tibet Plateau, particularly the Ali region, represents a unique and untapped natural laboratory for exploring the diversity of culturable actinobacteria and biologically active secondary metabolites. In this study, 10 different media were used to isolate actinobacteria from two soil samples collected from Ali region by selective cultural-based approaches. A total of 406 actinobacteria strains affiliated to 36 genera in 17 families of 9 orders were isolated. Totally 152 cultivable actinobacterial strains were selected for antimicrobial activity assay against "ESKAPE" pathogens. Sixty-three strains exhibited antagonistic activity against at least one of the tested pathogens, among them, 7 positive strains were identified by the "pDualrep2" system as either inhibitor of protein translation or DNA biosynthesis. An Amycolatopsis strain coded as A133, which exhibited a broader antimicrobial activity and a similar antimicrobial mechanism as the levofloxacin-induced expression of TurboRFP, was prioritized and further analyzed by omics tools for the prediction of bioactive compounds. Consequently, rifamycins and zampanolides were annotated by antiSMASH and GNPS (Global Natural Social Molecular Networking) analysis. By Chromatographic separation, such as Sephadex LH-20 and HPLC, and spectral analysis, such as NMR and UPLC-HRESI-MS/MS, five members of rifamycins, including rifamycin W, protorifamycin I, rifamycin W-M1, proansamycin B, and rifamycin S, were purified and identified from the cultural broth of the strain A133. Of particular interest was the discovery of rifamycin W-M1, a new member of the naturally occurring rifamycin group of antibiotics from the Amycolatopsis strain. Assisted by omics tools, the successful and highly efficient discovery of rifamycins, a group of clinically used antibiotics from actinobacteria in Ali area encouraged us to devote more energy to explore new antibiotics from the soils on the Western Tibetan Plateau.